Colectivos de inversión empresarial: una opción hacia el desarrollo local (2011)
This study aimed to structure the CIEM (Spanish acronym for Business Investment Group) model, which is geared to reducing poverty in each location that adapts the model to its local reality by creating new companies, strengthening those facing difficulties, and reopening companies that have been closed. It was carried out using the social method, based on an opinion poll conducted with potential entrepreneurs and a panel discussion composed of key actors. Their practical ideas, associated with theoretical analysis, led us to conclude that it is feasible to implement a three-dimensional business driving model: new business, enhanced business, and restarting business. These three business categories are supported by the joint efforts of entrepreneurs and investors for building local development.